Strategies to Increase Interest in Arabic Learning at Senior High School - Sutisna, Dede; Atha, Yusuf Ali Shaleh (UIN Sunan Gunung Djati Bandung, 2023)
Distinct challenges necessitating innovative strategies for heightened student interest and engagement mark Arabic language learning in senior high schools. This study addresses the imperative for practical and effective approaches to render Arabic learning more appealing, considering the diverse educational contexts and backgrounds of students in public senior high schools (SMA Negeri) and Madrasah Aliyah (MA). The study assesses current practices and challenges in Arabic language education by employing a comprehensive research methodology involving surveys, interviews, and classroom observations. It delves into students' preferences, learning styles, and the pedagogical methods employed by instructors in both SMA Negeri and MA. The research identifies pivotal strategies to augment interest in Arabic learning at senior high schools. Findings underscore the efficacy of integrating interactive and culturally relevant teaching materials, leveraging technology, and tailoring instructional methods to suit students' diverse backgrounds. Through a comparative analysis between SMA Negeri and MA, the study illuminates context-specific preferences and challenges. Contributing novelty to the field, this study offers nuanced insights into tailored strategies for enhancing interest in Arabic learning in senior high schools. Integrating interactive and culturally relevant elements aligns with contemporary educational approaches, providing a nuanced perspective on effective language instruction. Based on the research findings, recommendations are proposed, advocating for adopting culturally enriched teaching resources, integrating technology for interactive learning experiences, and customizing teaching approaches to accommodate the diverse student backgrounds in SMA Negeri and MA. Educational stakeholders are encouraged to implement these strategies to foster a more engaging and effective Arabic language learning environment in senior high schools.